2021
DOI: 10.1186/s13041-021-00794-7
|View full text |Cite
|
Sign up to set email alerts
|

Atg7 deficiency in microglia drives an altered transcriptomic profile associated with an impaired neuroinflammatory response

Abstract: Microglia, resident immunocompetent cells of the central nervous system, can display a range of reaction states and thereby exhibit distinct biological functions across development, adulthood and under disease conditions. Distinct gene expression profiles are reported to define each of these microglial reaction states. Hence, the identification of modulators of selective microglial transcriptomic signature, which have the potential to regulate unique microglial function has gained interest. Here, we report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 89 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…The ATG7 gene encodes an E1-like activating enzyme implicated in the regulation of organismal mitophagy ( Barrientos-Riosalido et al, 2023 ). Studies have shown that silencing ATG7 expression can slow the proinflammatory response of microglia, thereby slowing the progression of inflammation-mediated neurotoxicity during PD ( Burguillos et al, 2011 ; Friess et al, 2021 ). FADS2 is a fatty acid desaturase (FADS) gene family member.…”
Section: Discussionmentioning
confidence: 99%
“…The ATG7 gene encodes an E1-like activating enzyme implicated in the regulation of organismal mitophagy ( Barrientos-Riosalido et al, 2023 ). Studies have shown that silencing ATG7 expression can slow the proinflammatory response of microglia, thereby slowing the progression of inflammation-mediated neurotoxicity during PD ( Burguillos et al, 2011 ; Friess et al, 2021 ). FADS2 is a fatty acid desaturase (FADS) gene family member.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, microglial Agt5 knockdown was sufficient to trigger M1 microglial polarization, while upregulation of autophagy promoted microglial polarization toward the M2 phenotype [ 22 ]. Microglial Atg7 deficiency was associated with reduced microglia-mediated neurotoxicity resulting in impaired microglial proinflammatory response [ 56 ]. In the animal studies, microglial autophagy is important for refining synapses during development, and defects cause autism spectrum disorder-like behavior [ 23 ].…”
Section: Discussionmentioning
confidence: 99%